PENGARUH STANDAR AKUNTANSI PEMERINTAH, INTERNAL AUDIT, KUALITAS SUMBER DAYA MANUSIA, SISTEM INFORMASI AKUNTANSI, TEKNOLOGI INFORMASI, SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN DI INSTANSI PEMERINTAH DAERAH KOTA PADANG - Helmi Prila Aldino; Annisa Annisa; Dewi Zulvia (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2022)
The purpose of this study was to determine the effect of Government Accounting Standards, Internal Audit, the quality of human resources, Accounting Information Systems, Information Technology, internal control systems on the quality of financial reports in Padang city government agencies. The population in this study were all financial employees at Padang City Government agencies. Using convenience sampling technique was applied to determine the sample. The sample in this study were employees of the finance department at Padang city government agencies who met the criteria. The number of samples used was 142 respondents who were taken based on predetermined criteria. Data was collected by using a questionnaire measured by a Likert scale. The results showed that the accounting information system had a positive and significant effect on the quality of financial reports, which was indicated by a significant value of 0.00, while information technology had a positive and significant effect on the quality of financial reports, which was indicated by a significant value. of 0.01.